Enhanced adhesion and wear resistance of DLC films on AZ31 alloy achieved with high bias voltage - Haitao Li; Chong Liu; Pengfei Sun; Jingping Zhang (Heliyon)
Diamond-like carbon (DLC) films exhibiting high adhesion and exceptional wear resistance were successfully applied onto the AZ31 surface without a adhesive layer. The structural features of the film were examined utilizing Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), and Raman spectroscopy. Mechanical properties were evaluated through Nano-indentation testing, while adhesion was evaluated using a scratch tester. Residual stress was determined by Stoney's equation. The results indicate that utilizing a high substrate bias ranging from −500 to −800 V, results in the presence of multiple craters and dislocations, which contribute to the enhancement of high residual compressive stress and hardness in the DLC film. The heightened compressive stress effectively embeds carbon atoms into the surface of the soft AZ31, creating an interfacial layer that significantly improves adhesion and wear resistance of the film. In contrast, at moderate bias levels with a range from −300 to −500 V, an increase in substrate temperature leads to the expansion and discontinuation of adjacent layers that decreases the mechanical properties, adhesion, and wear resistance of the film. When at low bias levels between 0 and -300 V, the hardness, crack resistance, residual stress, and wear resistance all increase with increasing of bias. Additionally, in this work, the mechanisms of adhesion and wear for the biased film are analyzed.